Managing economic crises and their impact on the public in Mecca During the period (648 H-923H/1250 AD-1517) - Almuhailib, Abeer Fahad Abdulaziz (Dirasat: Human and Social Sciences, 2023)
Objectives: This research aims to identify the most important economic crises that Makkah experienced during the Mamluk era, and the extent of the impact of these crises on Makkah society, especially on its weakest group, which is the common category, It also aims to identify the most important reasons for the occurrence of these crises, and the most prominent efforts of the princes of Makkah and the Mamluk sultans in resolving these crises. Methods: The research followed the historical descriptive approach based on collecting historical material from its sources, then arranging and compiling it, and then relied on the analytical approach to find out the most prominent causes of these crises and analyze their results. Results: The research reached a set of important results: Among them is that imposing various and heavy taxes on the people of Makkah and its merchants was one of the most prominent causes of its economic crises, and these taxes are among the human causes. Among them are drought, floods, epidemics, and other environmental disasters that were among the natural causes that deepened the impact of the economic crises in Makkah. Conclusions: The economic crises that Makkah witnessed during the Mamluk era affected the weakest group of Meccans, namely the common people, and that the efforts of the princes of Mecca and the sultans of Egypt alleviated the severity of these crises as much as possible.